Analisis Dampak Pembangunan Industri dan Kebijakan Bank Tanah di Kabupaten Sidoarjo: Menuju Pengelolaan Tanah yang Berkelanjutan - Rahmadhani, Shelvia Agustine; Fitrianto, Achmad Room (Jurnal E-Bis, 2024)
The rate of increase in population in Sidoarjo Regency continues to increase, and Sidoarjo Regency has medium and large industrial areas spread across 18 sub-districts. Of course, this will have an impact on changes in land use in Sidoarjo Regency. In this way, the increasing demand for land in Sidoarjo Regency is not only for meeting residential needs, but also for development in the industrial sector. The increase in demand for land will result in the availability of land becoming scarce, land market prices unstable, and various kinds of problems will arise. Seeing these problems, research was used to review whether the Land Bank concept could be a solution. The method used in this research is descriptive quantitative. The presence of the Land Bank is considered as a way to make land management more productive. By implementing the Land Bank concept in Sidoarjo Regency, inefficient land use can be minimized and the amount of land for the future can be maintained.